2012
DOI: 10.1097/dcr.0b013e3182351c1f
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Oncologic Outcomes After Abdominoperineal Resection Compared With Restorative Resection for Low Rectal Cancer

Abstract: Technical factors alone are unlikely to be responsible for the worse outcomes after abdominoperineal resection in comparison with restorative resection. A combination of patient- and tumor-related factors that may have indicated the choice of the procedure also probably contribute to the worse outcomes. Because patients undergoing abdominoperineal resection represent a high risk for poor outcomes, management strategies need to consider all these factors during treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
31
0
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
2
31
0
5
Order By: Relevance
“…However, in comparison with a standard APR, the recent cylindrical APR technique removes 8e20 mm of additional lateral tissue from the internal sphincter 29 and a further distal margin of approximately 20 mm. 30 After a systematic review, Pahlman 31 undertook a selection process to decide between an anterior resection and an APR for the low rectum according to the risk of margin involvement and suggested opting for an APR for radioresistant cancer and/or a large fixed T4. Our study confirmed that 2 or 3 variables indicated a high risk of CRMþ (50%) after sphincter-sparing surgery and that a radical operation therefore seems to be possible only with an APR.…”
Section: Discussionmentioning
confidence: 99%
“…However, in comparison with a standard APR, the recent cylindrical APR technique removes 8e20 mm of additional lateral tissue from the internal sphincter 29 and a further distal margin of approximately 20 mm. 30 After a systematic review, Pahlman 31 undertook a selection process to decide between an anterior resection and an APR for the low rectum according to the risk of margin involvement and suggested opting for an APR for radioresistant cancer and/or a large fixed T4. Our study confirmed that 2 or 3 variables indicated a high risk of CRMþ (50%) after sphincter-sparing surgery and that a radical operation therefore seems to be possible only with an APR.…”
Section: Discussionmentioning
confidence: 99%
“…5-летняя выживаемость составляет 71-79,8 % при ССО и 56-78,7 % при БПЭ [25,46]. Безрецидивная выживаемость составляет 70-78 % для пациен-тов, перенесших ССО и 54-80 % для пациентов, которым выполнялась БПЭ [46,65]. Частота местного рецидива 3-8,9 % при ССО и 4-13,5 % при выполнении БПЭ [9, 24,25,46,65].…”
unclassified
“…Безрецидивная выживаемость составляет 70-78 % для пациен-тов, перенесших ССО и 54-80 % для пациентов, которым выполнялась БПЭ [46,65]. Частота местного рецидива 3-8,9 % при ССО и 4-13,5 % при выполнении БПЭ [9, 24,25,46,65]. Ме-диана до развития рецидива составила 13-18 месяцев для ССО и 17 месяцев для БПЭ, без-рецидивная выживаемость -121-135 месяцев в группе ССО и 100 месяцев в группе БПЭ [9].…”
unclassified
See 2 more Smart Citations